Nonlinear convective heat transport in multiple magnetized electron temperature filaments - Sydora, R.D.; Van Compernolle; Karbashewski, S.; Morales, G.J.; Maggs, J.E. (Вопросы атомной науки и техники, 2017)
Results are presented from a basic electron heat transport experiment consisting of multiple magnetized electron temperature filaments in close proximity. This arrangement samples cross-field transport from nonlinear drift-Alfven waves and is used to study elements of chaotic heat flow. Experiments are performed in the Large Plasma Device (LAPD) at the University of California. A biased LaB₆ cathode injects low energy electrons (below ionization energy) along a strong magnetic field into a pre-existing large and cold plasma forming an electron temperature filament embedded in a colder plasma, and far from the machine walls. A carbon masking plate with several holes is used to create 3 electron temperature filaments. Drift-Alfven and thermal waves from a single filament have been characterized and compared to previous studies with a different electron beam source. The 3-filament case exhibits a complex wave pattern and enhanced cross-field transport. Представлены результаты изучения переноса тепла между несколькими замагниченными нитями с электронной температурой, находящимися в непосредственной близости. Такое расположение позволяет изучать перенос тепла поперек поля из-за нелинейных дрейфово-альфвеновских волн и используется для изучения составных частей хаотического теплового потока. Эксперименты проводятся на LAPD (Large Plasma Device) в Университете Калифорнии. Смещённый LaB₆-катод инжектирует низкоэнергетичные электроны (ниже энергии ионизации) вдоль сильного магнитного поля в предварительно созданную холодную плазму больших размеров и создаёт вкраплённые нити электронной температуры вдали от стенок камеры установки. Углеродная накладка с несколькими отверстиями используется для создания трёх нитей с электронными температурами. Изучены дрейфово-альфвеновские и тепловые волны от одной нити и проведено сравнение с предыдущими результатами, полученными в другом источнике электронов. Случай с тремя нитями демонстрирует сложную волновую картину и повышенный перенос поперёк поля. Представлено результати вивчення перенесення тепла між декількома замагніченими нитками з електронною температурою, які знаходяться в безпосередній близькості. Таке розташування дозволяє вивчати перенесення тепла поперек поля через нелінійні дрейфово-альфвенівські хвилі та використовується для вивчення складових частин хаотичного теплового потоку. Експерименти проводяться на LAPD (Large Plasma Device) в Університеті Каліфорнії. Зміщений LaB₆-катод інжектує низькоенергетичні електрони (нижче енергії іонізації) уздовж сильного магнітного поля в попередньо створену холодну плазму великих розмірів і створює украплені нитки електронної температури далеко від стінок камери установки. Вуглецева накладка з декількома отворами використовується для створення трьох ниток з електронними температурами. Вивчено дрейфово-альфвенівські та теплові хвилі від однієї нитки та проведене порівняння з попередніми результатами, що отримані в іншому джерелі електронів. Випадок з трьома нитками демонструє складну хвильову картину і підвищений перенос поперек поля.